Three new species of Barleeidae (Mollusca, Gastropoda, Rissooidea) from Brazil - Absalão, Ricardo Silva (Zootaxa, 2002)
Three new species of the Barleedidae are described from Brazilian waters. Caelatura tigrina n.sp. from Davis Seamount (20°39’ S / 034°43’ W) is diagnosed by 5 narrow well-spaced spiral cordlets in each whorl and its golden-brown color with white axial flames. Caelatura especulabunda n.sp from Dogaressa Seamount (20°51’ S / 033°45’ W) is diagnosed by its shell oval-pupoid with slightly convex whorls and 9-10 close, thick, spiral cordlets. Protobarleeia pyrrocincta n.sp. from Abrolhos Bank (about 19° S, 38° W), the first report of the genus from South Western Atlantic, is diagnosed by its reddish belts.